PERLINDUNGAN HUKUM TERHADAP PEREMPUAN PEMBELA HAK ASASI MANUSIA DI INDONESIA - Tompul, Verawati BR (Collegium Studiosum Journal, 2025)
Women human rights defenders are agents of change, defending the interests of citizens and groups who often have no access to justice. When women human rights defenders assist a community or group, they are highly vulnerable to threats, including sexual harassment, rape threats, death threats, frequent reporting to the police by the other party, cyber attacks, physical, psychological and verbal abuse, defamation, attacks on family and murder. The vulnerability experienced by PPHAMs is a form of structural violence rooted in a patriarchal legal and social system. The state has a duty to protect PPHAM, i.e. to create a safe and comfortable environment for them. To protect PPHAM from criminalisation. The legal protection of PPHAM must be a priority for the state and civil society to ensure a safe and just space.